Pengaruh Penanganan Pascapanen dan Pola Supply Chain Management (SCM) terhadap Pendapatan Petani Beras Hitam di Kabupaten Sukabumi: The Effect of Postharvest Handling and Supply Chain Management (Scm) Pattern on Black Rice Farmers in Sukabumi Distric - Kartika Rini, Neneng; Sofiani, Venita (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2018)
Black Rice is a local commodity which apparently was not found in the Ciemas area of Sukabumi Regency alone, in several Districts in Sukabumi Regency, namely in the Districts of Waluran, Cidolog, and Kabandungan. Black rice from the nutritional content and benefits is no less significant. Black Rice prices are higher than white rice or consumption rice. Every Black Rice farmer still has problems in carrying out the postharvest handling process. This is the case with Chain Management (SCM) or supplies chain management by farmers; farmers also do this with different patterns. The income of lowland rice farmers is uncertain. Because the benefits of black rice and farmers' income fluctuate every year, it is necessary to check postharvest handling and to know and analyze how efficient workflows are to accelerate supply chain management, black rice reaches consumers and makes more enormous profits. Rather than spending money on black rice entrepreneurs. The results show that the postharvest handling process and the SCM pattern affect the income of farmers in Waluran, Ciemas, Surade, Cidolog, and Kabandungan, Sukabumi Regency.